Metabolic syndrome – cardiac structure and functional analysis by echocardiography; a cross sectional comparative study - Sakthivadivel, Varatharajan; Chinnathambi, Chennappan; Selvaraju, Divya; Gaur, Archana; Bakthavatchalam, Ramya; Srivijayan, Appandraj; Sundaramurthy, Raja; Tadi, Lakshmi Jyothi; John, Nitin Ashok (Hormone molecular biology and clinical investigation, 2023)
Metabolic syndrome (MS) is a collection of metabolic disorders including hyperglycemia, hypertension and dyslipidemia. The outcome of metabolic syndrome depends on structural changes in heart like increased left atrial size or increased left ventricular mass. This study was done to determine the echocardiography abnormalities in metabolic syndrome. After obtaining informed consent, 75 subjects with metabolic syndrome and 75 controls were included in the study. 2D echo/M mode examination was performed for all. Aortic root, left atrial size, left atrial volume, septal wall thickness during systole (SWs) and diastole (SWd), posterior wall thickness during systole (PWs) and diastole (PWd), left ventricle dimension during systole (LVDs) and diastole (LVDd), and ejection fraction were measured. The values were compared between the groups. After adjustment for age, sex, smoking, alcohol and BMI; left ventricular diameter in systole and diastole was significantly more than controls (p<0.001); HR of 1.29 (95% CI 1.13-1.46), 1.29 (95% CI 1.15-1.45) respectively. Left ventricular mass and left atrial volume were increased significantly in subjects with metabolic syndrome (p<0.001); HR were 1.06 (95% CI 1.03-1.08), 1.13 (95% CI 1.06-1.19) respectively. Ejection fraction was low normal in subjects with metabolic syndrome compared to controls (p<0.05); HR 0.90 (95% CI 0.83-0.98). Cardiac abnormalities were common in subjects with metabolic syndrome, predominantly affecting the left ventricular mass, diameter and left atrial volume. Early life style modifications are essential to prevent these complications.